Determinants of legal protection to improve MSMEs development - Amri, Faisal; Hamdani, Deky; Maryanto, Maryanto; Sari, Ayu Esteka (International Journal of Enterprise Modelling, 2025)
Determinant Legal Protection consists of business licenses, distribution permits, registered trademarks, and legality of business entities. From a theoretical perspective, this research contributes a novel integrated model that connects legal protection with MSME growth via digital platforms. It advances the literature by framing digitalization not only as a technological or market tool but as a strategic outcome of legal infrastructure. By quantifying both direct and indirect effects within a Structural Equation Modeling (SEM) framework, this study strengthens empirical understanding of how regulatory formalization supports enterprise digitalization and growth. This model can be adapted or extended for cross-regional or sectoral studies in emerging markets. From a practical standpoint, the findings underscore that legal formalization—when combined with digital platform readiness—produces greater developmental impacts on MSMEs. Policymakers and stakeholders should therefore prioritize joint initiatives that streamline legal registration while simultaneously enabling digital onboarding, such as e-license platforms linked to e-commerce or fintech ecosystems. The research uses quantitative research, utilizing descriptive and inferential analysis through the Structural Equation Modeling (SEM) technique. The utilized data comprises both primary and secondary sources, employing data collection methods such as questionnaires. MSME actors in Sungai Penuh City with a total of 150 are the sample of this study. The result of this study, business licenses, distribution permits, registered trademarks, and legality of business entities have proven to have a significant effect on legal protection. Legal protection has a positive and significant effect on digital trading platforms and MSME development.